Triangulation algorithms for generating as-Is floor plans - Brandão, F.; Paio, A.; Lopes, A. (Nexus Network Journal, 2020)
Precisely capturing context is a fundamental first step in dealing with built environments. Previous research has demonstrated that existing methods for generating as-is floor plans of non-orthogonal rooms by non-expert users do not produce geometrically accurate results. The present paper proposes the adaptation of empirical triangulation methods, traditionally used by architects and other building professionals in surveying building interiors, to the development of semi-automated workflow of room survey. A set of triangulation algorithms that automate the plan drawing stage are presented.